Winter home range and habitat use by porcupines in Alaska1. Issue 3 (4th October 2012) - Coltrane, Jessica A.; Sinnott, Rick
Abstract: Habitat selection results from trade‐offs between availability and use of resources under constraints of predation, competition, or other threats, which can vary spatially and temporally. For northern herbivores, winter food availability and quality can limit population size and may drive habitat preference. North American porcupines ( Erethizon dorsatum ) are widespread generalist herbivores that range from Mexico to the northern reaches of Alaska. During the long Alaskan winter, porcupines deal with high energetic demands resulting from low ambient temperatures while subsisting on low quality forage. We tracked free‐ranging porcupines over 3 winters in southcentral Alaska to determine habitat selection and home range size in relation to diet. Porcupines maintained larger than expected home ranges, and selected for conifer‐hardwood forests at the home range level. Individual variation among porcupines was too large to determine a pattern of microhabitat selection among trees. Regardless, direct observations revealed that porcupines used only white spruce and paper birch trees for foraging. White spruce may provide some nutritional and thermoregulatory advantage over paper birch; however, porcupines did feed on paper birch cambium, suggesting some nutritional requirement is met by eating paper birch. Porcupines most likely feed on paper birch cambium when detoxification pathways used to process plant toxins in white spruce needles are saturated. Maintaining mixed conifer‐hardwood forests in southcentral Alaska would provide suitable winter habitat for porcupines and may alleviate damage to single species stands of conifers or hardwoods that are preferred by commercial forestry operations. © 2012 The Wildlife Society.